A Combinatorial Approach to Obtain the Yield Probability Distribution along a Linearly-Loaded Cantilever Beam - Baghdad Science Journal (مجلة بغداد للعلوم, 2016)
The substantial key to initiate an explicit statistical formula for a physically specified continua is to consider a derivative expression, in order to identify the definitive configuration of the continua itself. Moreover, this statistical formula is to reflect the whole distribution of the formula of which the considered continua is the most likely to be dependent. However, a somewhat mathematically and physically tedious path to arrive at the required statistical formula is needed. The procedure in the present research is to establish, modify, and implement an optimized amalgamation between Airy stress function for elastically-deformed media and the multi-canonical joint probability density functions for multivariate distribution completion, so that the developed distribution is to exhibit a sophisticated illustration of yield probability distribution along a cantilever beam whose structure is subjected to a linearly-distributed load. This combinatorial approach is to clarify the intensity of the stresses exerted onto the beam, to standardize the terms of stresses and their affection and to convert them into a more significant depiction of a probability distribution.